Why should you reverse the order when dividing a fraction? A study of pre-service mathematics teachers' pedagogical content knowledge in fractional concept. (July 2020) - Apsari, R A; Sariyasa, S; Indrawan, G; Maulyda, M A; Radiusman, Radiusman
Abstract: This study was a part of larger study in examining pre-service mathematics teachers' Pedagogical Content Knowledge. The aim of the present study was to elaborate the prospective teachers' conceptual understanding in fraction and how they will teach it for the students. There were 50 participants in this study, all of them are the final year students of mathematics education study program of a state university in Bali who already took the teaching internship program in the school. The data were collected through written test and continued by interview with the participants. The data were analysed qualitatively using descriptive method. From the result, it is found that the prospective mathematics teachers have a difficulties in understanding the concept of fraction. It leads to the lack comprehension in teaching the concept to the students. Reflect to the result, it is recommended to the teacher training institution to emphasize the big ideas in school mathematics' topics to ensure the prospective teachers have a sufficient knowledge to teach mathematics meaningfully.